ApoB100 remodeling and stiffened cholesteryl ester core raise LDL aggregation in familial hypercholesterolemia patients - Maria Teresa La Chica Lhoëst; Andrea Martínez; Eduardo Garcia; Jany Dandurand; Anna Polishchuk; Aleyda Benitez-Amaro; Ana Cenarro; Fernando Civeira; Amable Bernabé; David Vilades; Joan Carles Escolà-Gil; Valerie Samouillan; et al. (Journal of Lipid Research)
Patients with familial hypercholesterolemia (FH) exhibit a significant residual cardiovascular risk. A new cardiovascular risk factor is the susceptibility of individual LDL particles to aggregation. This study examined LDL aggregation and its relationship with LDL lipid composition and biophysical properties in patients with FH compared to controls. LDL aggregation was measured as the change in particle size, assessed by dynamic light scattering, after exposure to sphingomyelinase, which breaks down sphingomyelin in the LDL phospholipid layer. Dynamic light scattering and transmission electron microscopy showed that LDL in FH patients exhibited smaller size and greater susceptibility to aggregation. Biochemical analyses revealed a higher cholesteryl ester (CE)/ApoB100 ratio in LDL from FH patients. Differential scanning calorimetry showed that LDL from FH patients had higher transition temperatures, indicating a more ordered CE core. Fourier transform infrared spectroscopy revealed fewer flexible α-helices (1658 cm⁻1) and more stable α-helices (1651 cm⁻1) in ApoB100 of LDL from FH patients. These structural changes correlated with higher CE content and increased LDL aggregation. In conclusion, a more ordered CE core in smaller LDL particles, combined with a higher proportion of stable α-helices in ApoB100, promotes LDL aggregation in FH patients. These findings suggest ApoB100 conformational structure as a new potential therapeutic targets within LDL to reduce cardiovascular risk in FH patients.